Blood brain barrier and inflammation in depression - Eva M. Medina-Rodriguez; Eléonore Beurel (Neurobiology of Disease, 2022)
The blood brain barrier (BBB) is a vital structure to protect the brain, tightly filtering the passage of nutrients and molecules from the blood to the brain. This is critical for maintaining the proper functioning of the brain, and any disruption in the BBB has detrimental consequences often leading to diseases. It is not clear whether disruption of the BBB occurs first in depression or is the consequence of the disease, however disruption of the BBB has been observed in depressed patients and evidence points to the role of important culprits in depression, stress and inflammation in disrupting the integrity of the BBB. The mechanisms whereby stress, and inflammation affect the BBB remain to be fully understood. Yet, the role of cytokines in regulating tight junction protein expression seems crucial. Altogether, the findings in depression suggest that acting at the BBB level might provide therapeutic benefit in depression.